Last Cruise of the Schooner "Chance" (May 1950) / I. Baltra.
Articulo con informacion sobre varias islas de Galapagos: Baltra, Isabela, Floreana, Fernandina, Santiago
Inglés
Keywords: Baltra; Isabela; Floreana; Fernandina; Santiago